Foreign Banks and Credit Dynamics in CESEE - Arakelyan, Maria (IMF Working Papers; Working Paper ;, 2018)
We use bank-level data on 16 CESEE economies over 2005-2014 to assess the role of foreign banks in the region's credit dynamics. We confirm that macroeconomic fundamentals of both host and home countries matter, as do the bank and parent bank characteristics. Moreover, we take a new approach by studying the drivers of differential credit growth between parent banks and their foreign subsidiaries. Host country macroeconomic fundamentals cease to play a significant role, while bank-level characteristics and in particular parent bank-level characteristics remain important. From policymakers' perspective, the paper provides further empirical evidence on the importance of monitoring the health of foreign parent banks as well as the potential regulatory changes in their home jurisdictions.